One-Pot Synthesis of α,β-Unsaturated Esters, Ketones, and Nitriles from Alcohols and Phosphonium Salts - Ding, Weijie; Hu, Juan; Jin, Huile; Yu, Xiaochun; Wang, Shun (Synthesis, 2018)
A general method for the synthesis of α,β-unsaturated esters, ketones, and nitriles is successfully achieved by a one-pot copper-catalyzed oxidation with O2 in air as oxidant. The solvent mixture of acetonitrile and formamide (1:1) is optimized to ensure the oxidation of alcohols, deprotonation of phosphonium salt, and Wittig reaction occur efficiently in one pot. A broad range of substrates has been explored for this process, including three electron-withdrawing group (CO2Et, COPh, CN) functionalized phosphonium salts. They reacted not only with benzylic and heteroaromatic alcohols, but also with aliphatic alcohols, forming the corresponding α,β-unsaturated esters, ketones, and nitriles in moderate to excellent yields.
Keywords: oxidation of alcohols; phosphonium salts; tandem reaction; copper catalyst; Wittig reaction; carbon–carbon double bond